Go Health (New Product Development Report) / Adam Farhat Saiful Arzuan ... [et al.]. - Saiful Arzuan, Adam Farhat; Shahrulazman, Amirah Batrisyia; Normizam, Nik Qistina Arissa; Muhammad Yusri, Nur Aina Syafiah; Zahari, Nur Syahirah Hanim; Marnyi, Nurul Farhanah (2023)
Our cutting-edge health app is a ray of convenience, accessibility, and patient empowerment in a time of rapid technological advancement and increased emphasis on personalized healthcare. Our health app is a comprehensive solution that offers quick access to medical services, education, and convenience. Its intuitive interface smoothly incorporates necessary features to improve the patient’s experience as a whole. This health app’s main objective is to remove the logistical barriers people encounter when trying to access healthcare. The app greatly lessens the inconvenience of making in-person clinic visits by allowing users to access these services via their smartphones. This method not only saves time but also lessens the requirement for medical certifications, enabling people to effectively manage their health issues without sacrificing their academic or professional obligations. "Go Health" makes sure that healthcare services are always accessible to users, regardless of their location or schedule.